The “Sea Factor” in Regional Cooperation: The Impact of the Russo-Ukrainian War - Ківалов, Сергій Васильович; Ківалов, С. В.; Кивалов, Сергей Васильевич; Kivalov, Serhii V.; Kivalov, Sergiy (My University, 2023)
The “sea factor” has a crucial influence on coastal states’ domestic and foreign policies, and may create additional incentives for regional cooperation and integration. The Russo-Ukrainian War, the largest armed conflict in Europe since World War II, has become a stress test for many regional transport and infrastructure projects. Moreover, this armed conflict has had different effects in different cases. For the Three Seas Initiative, the Russo-Ukrainian war became an additional incentive to strengthen cooperation. It gave the initiative new eaning and even stimulated its expansion through the decision to grant partner status to Ukraine. At the same time, this conflict had negative consequences for China’s Belt and Road Initiative (BRI). The war also led to the emergence of another area of cooperation between Ukraine and Turkey in the Black Sea Grain Initiative.
Kivalov S. The “Sea Factor” in Regional Cooperation: The Impact of the Russo-Ukrainian War / Sergiy Kivalov,. - Lex Portus. - 2023. - Vol.9. - Iss. 2. - P. 19-27.
Keywords: Three Seas Initiative; BRI; Black Sea Grain Initiative; Ukraine; Russia; war; armed conflict; збройний конфлікт; війна; Росія; Україна; Чорноморська морська ініціатива; ініціатива трьох морів